2017
DOI: 10.1002/mgg3.300
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Alu element‐mediated deletion in the promoter region of GNE in siblings with GNE myopathy

Abstract: Background GNE myopathy is a rare genetic disease characterized by progressive muscle atrophy and weakness. It is caused by biallelic mutations in the GNE gene that encodes for the bifunctional enzyme, uridine diphosphate (UDP)‐N‐acetylglucosamine (GlcNAc) 2‐epimerase/N‐acetylmannosamine (ManNAc) kinase. Typical characteristics of GNE myopathy include progressive myopathy, first involving anterior tibialis muscle and sparing the quadriceps, and rimmed vacuoles on muscle biopsy. Identifying biallelic mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…The second causal variant was inferred from the combination of aCGH and RNA-seq that definitively diagnosed the case as GNE-related myopathy, and led to identification of multiple gene expression perturbations. This study shows the involvement of quadriceps muscle directly with both rimmed vacuoles and inflammation, unlike previous reports of individual cases and cohorts, 22,23,26,27 enhancing the molecular-pathological spectrum of GNE-myopathy that is important to understand for patient stratification in clinical trials.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…The second causal variant was inferred from the combination of aCGH and RNA-seq that definitively diagnosed the case as GNE-related myopathy, and led to identification of multiple gene expression perturbations. This study shows the involvement of quadriceps muscle directly with both rimmed vacuoles and inflammation, unlike previous reports of individual cases and cohorts, 22,23,26,27 enhancing the molecular-pathological spectrum of GNE-myopathy that is important to understand for patient stratification in clinical trials.…”
Section: Discussioncontrasting
confidence: 82%
“…Recently, a~11.3-kb deletion encompassing exon 2 was found in a patient along with a single V727M variant. 22 In our study, aCGH revealed a novel 7.08 kb deletion (g.36,259,402 to g.36,266,483) (SCV000599234) upstream of the GNE gene (different from deletions identified in Zhu et al 23 ) (Fig. 2B).…”
Section: Exome and Rna Sequencing Revealed Monoallelicsupporting
confidence: 50%
See 2 more Smart Citations
“…There are ethnic GNE founder mutations found in Middle Eastern (Met743Thr), Japanese (Cys44Ser, Asp207Val, and Val603Leu), Roma Bulgarian (Ile618Thr) and Indian/Asian (Val727Met) populations ( Table 1). Besides founder mutations, there are more than 200 GNE gene mutations reported in over 950 GNE myopathy patients worldwide, in either the epimerase or the kinase encoding domains of the enzyme [20,31,76,77], several proven to result in decreased enzyme activity [31,33,57]. Most pathogenic mutations that cause GNE myopathy are missense, but nonsense mutations, insertion/deletions, and intronic (splice site) variants have also been described [76,77].…”
Section: Muscle Histologymentioning
confidence: 99%